2023
DOI: 10.1126/scisignal.abo3406
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog-induced ZFYVE21 promotes chronic vascular inflammation by activating NLRP3 inflammasomes in T cells

Abstract: The zinc finger protein ZFYVE21 is involved in immune signaling. Using humanized mouse models, primary human cells, and patient samples, we identified a T cell–autonomous role for ZFYVE21 in promoting chronic vascular inflammation associated with allograft vasculopathy. Ischemia-reperfusion injury (IRI) stimulated endothelial cells to produce Hedgehog (Hh) ligands, which in turn induced the production of ZFYVE21 in a population of T memory cells with high amounts of the Hh receptor PTCH1 (PTCH hi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 67 publications
7
19
0
Order By: Relevance
“…While induction of inflammasome proteins canonically occurs following PAMP-induced NF-κB, this process may be subsumed by endogenous molecules including reactive oxygen species, metabolites, and hypoxia during sterile inflammation associated with transplant rejection 38 . Various cytokines including IFN-γ, though dispensable for IL-1β production in human macrophages, may similarly prime NLRP3 inflammasomes 39 , a process that we found occurs following EC-mediated direct allorecognition in vitro and in various humanized mouse models including coronary artery xenografts 2 , 9 , 40 in vivo. While abundant IFN-γ is induced in our in vitro and in vivo approaches above, our studies do not rule out the contribution(s) from other endogenous molecules eliciting inflammasome priming.…”
Section: Discussionmentioning
confidence: 55%
“…While induction of inflammasome proteins canonically occurs following PAMP-induced NF-κB, this process may be subsumed by endogenous molecules including reactive oxygen species, metabolites, and hypoxia during sterile inflammation associated with transplant rejection 38 . Various cytokines including IFN-γ, though dispensable for IL-1β production in human macrophages, may similarly prime NLRP3 inflammasomes 39 , a process that we found occurs following EC-mediated direct allorecognition in vitro and in various humanized mouse models including coronary artery xenografts 2 , 9 , 40 in vivo. While abundant IFN-γ is induced in our in vitro and in vivo approaches above, our studies do not rule out the contribution(s) from other endogenous molecules eliciting inflammasome priming.…”
Section: Discussionmentioning
confidence: 55%
“…DGF is a common manifestation seen after renal transplantation and always occurs after severe IRI ( 30 ). Therefore, we aimed to develop a predictive model for DGF based on the NR-DEGs from the GSE43974 dataset.…”
Section: Resultsmentioning
confidence: 99%
“…CD4 + T cells, while lacking primary cilium, organelles mediating Hh signaling, highly express Hh pathway components, including Ptch, Smo, and Gli effectors, and are capable of both receipt and transmission of Hh inputs, possibly via signals derived from immune synapses ( 23 ). Hh signaling encodes programs for positive costimulation ( 24 , 25 ) to regulate type 1 ( 14 ), Th2 ( 26 ), Treg ( 27 ), and Th17 ( 28 ) effector polarization.…”
Section: Introductionmentioning
confidence: 99%
“…We previously explored this notion using a humanized mouse model incorporating IRI-treated human coronary artery xenografts ( 14 , 15 ). We found that soluble and surface-bound Hh ligands, including Sonic, Desert, and Indian Hedgehog, were upregulated by complement membrane attack complexes (MACs) during the reperfusion phase of IRI, and the same Hh ligands delivered costimulatory but not mitogenic signals to memory CD4 + CD45RO + T cells (Tmem), endowing these cells with heightened effector and migratory responses ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation